Implant success and survival rates in daily dental practice: 5-year results of a non-interventional study using CAMLOG SCREW-LINE implants with or without platform-switching abutments - Sven Marcus Beschnidt; Claudio Cacaci; Kerem Dedeoglu; Detlef Hildebrand; Helfried Hulla; Gerhard Iglhaut; Gerald Krennmair; Markus Schlee; Paul Sipos; Andres Stricker; Karl-Ludwig Ackermann (SpringerOpen, 2018)
Abstract Background The performance of dental implants in controlled clinical studies is often investigated in homogenous populations. Observational studies are necessary to evaluate the outcome of implant restorations placed in real-life situations, according to standard practice, and to assess the needs of the patients. The aim of this non-interventional study was to reveal the survival, success, and general performance of CAMLOG SCREW-LINE implants and their restorations in daily dental practice. Methods Seventeen private practices across five countries participated in this prospective multicenter study. Patients received implants in the maxilla and mandible which were restored either with platform-matching or platform-switching abutments. Patients were followed-up for up to 5 years post-loading. Radiographs and clinical parameters were evaluated and patient satisfaction was evaluated. Results From a total of 196 patients planned, 185 patients with 271 implants were restored with abutments and fulfilled the follow-up inclusion criteria. Three implant failures were recorded, resulting in a cumulative survival rate of 98.6% after 5 years post-loading. One persistent complication of peri-implantitis occurred. The soft tissue health remained stable, and the papilla height improved after loading. At 5-year follow-up, the mean crestal bone loss was − 0.28 ± 0.60 mm; over 99% of patients reported satisfaction with the restoration as excellent or good. Conclusions Implants placed and restored with both platform-matching and platform-switching abutments in daily dental private practice achieved excellent clinical outcomes with highly satisfied patients after 5 years of function, confirming the results obtained in well-controlled clinical trials.